Analisis Tingkat Kebisingan Dan Gangguan Pendengaran Pada Pekerja Tambang Emas Di Desa Lebong Tandai - Agus Widada; Ferona Amanda Nadya (Jurnal Sanitasi Profesional Indonesia, 2026)
This research is based on the high use of rolling machines in the gold processing process, which operate 24 hours a day and produce noise levels exceeding the threshold limit (TLV) for quality standards. Excessive noise exposure is known to cause hearing loss in workers. This study aimed to analyze noise levels and hearing loss among gold mine workers in Lebong Tandai Village, North Bengkulu Regency. The research method used a field survey and hearing loss examinations. The examination results showed that of the 72 workers, 22 had normal hearing, 23 had mild hearing loss, 22 had moderate hearing loss, and 9 had severe hearing loss. The primary factor causing hearing loss was noise intensity exceeding quality standards. This study recommends the need for noise prevention and control efforts in the mining workplace, as well as regular hearing health examinations to minimize the risk of hearing loss among gold mine workers in Lebong Tandai Village.